2015
DOI: 10.1044/2015_aja-14-0086
|View full text |Cite
|
Sign up to set email alerts
|

SoundSpace Online: The Development of an Online Resource About Hearing Loss

Abstract: The literature and the range of interest have illustrated the need for an up-to-date website providing information and resources on hearing loss. Challenges include monitoring and keeping the website up to date; in this article, a plan of action is discussed. The website is currently in development, with plans for a launch in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…An expert panel consisting of senior academic staff members, researchers and experienced ED clinical staff to assess the online learning resource for content and construct validity. This involved critical appraisal of the site ISSN:2184-044X ISBN:978-989-54312-6-7 © 2019 and constructive feedback in relation to visual appeal, ease of navigation, currency, relevance and accuracy of content and perceived usefulness (Ng et al 2015). The expert panel were also asked to provide suggestions for improvements so that modifications could be made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An expert panel consisting of senior academic staff members, researchers and experienced ED clinical staff to assess the online learning resource for content and construct validity. This involved critical appraisal of the site ISSN:2184-044X ISBN:978-989-54312-6-7 © 2019 and constructive feedback in relation to visual appeal, ease of navigation, currency, relevance and accuracy of content and perceived usefulness (Ng et al 2015). The expert panel were also asked to provide suggestions for improvements so that modifications could be made.…”
Section: Discussionmentioning
confidence: 99%
“…Following a successful grant application, an expert web designer was engaged to create and develop a visually appealing and easy to navigate site (Maycock et al 2012). It was essential to ensure that the website was clear, easily understood, relevant and up to date (Ng, Archbold, Mayer and Mulla 2015). The website homepage contains an introductory video and instructions on how to navigate the site.…”
Section: Design and Development Of The Websitementioning
confidence: 99%
“…Evaluating the eHealth literacy of the target group, with one of the several validated instruments already available (e.g., [ 120 ]), and developing eHealth services accordingly is central for user involvement and empowerment. In addition to complex language, other barriers for implementing online information can be outdated websites [ 121 ], disabilities preventing patients to understand the online information such as visual or cognitive impairment [ 88 ], difficulties in navigation and low computer skills [ 119 , 122 ]. For example, Eikelboom and Atlas [ 123 ] showed that patient involvement in eHealth was highly facilitated by previous awareness and knowledge of eHealth services and technology so user involvement by design should be considered in order to develop useful, effective solutions for patient education.…”
Section: Discussionmentioning
confidence: 99%